The Existence of Women in the Pre- and Post-Reformation Period in The Novel Laut Bercerita: A Review of Feminism - Roh Jung Ju; M. Yoesoef M. Yoesoef; Turita Indah Setyani (International Journal of Science and Applied Science: Conference Series, 2022)
Women are faced with various stereotypes of being second-class beings. The female must accept being a being who must be under the position of the male. However, in contrast to such stereotypes, literary works are able to show a deconstruction of the conditions and situations of women as empowered beings. This is illustrated through one of Indonesia's novels entitled Laut Bercerita by Leila S. Chudori. Women are described as figures who have a role to be able to show their existence even though at that time there was political turmoil before 1998. One of the important things that deconstructs stereotypes is the existence of strong women who are able to heal male characters through their efforts. Women who are usually used as second sex in patriarchal confines seek to be undermined in the narrative of the novel. Based on this, the purpose of this study is to dismantle the existence of women in the time of turmoil before and after the reformation in the novel Laut Bercerita. This research is a qualitative descriptive study with the approach of Simon de Beauvoir existentialist feminism. The results of this study show that women managed to get out of the notion of second sex by showing existence in the public domain by getting a proper education and job in the public domain, being able to struggle to find their brother's character and her brother's colleague who were victims of student disappearance in 1998, being able to cure men due to kidnapping and torture in 1998, and the struggle to get information on the development of cases of losing older siblings  and his brother's partner in the period before 1998.